Percepción del funcionamiento familiar y resiliencia en adolescentes tardíos de Lima Metropolitana - Valdez Olivari, Ana Lucia (2021)
The present research seeks to generate greater knowledge about the positive resources and capacities that every individual has and the role that family function plays during their development in late adolescence. Therefore, this study aimed to determine the extent to which family functionality predicts resilience in late adolescents from Metropolitan Lima. A total of 346 students from private schools, both females and males, between the ages of 15 and 18 were evaluated through the Resilience Scale (RS) developed by Wagnild & Young and Smilkstein’s Family APGAR. Since the psychometric properties of the RS were not clear, it was established as a preliminary objective to analyse its properties. The results obtained indicate that the RS´s internal structure maintains a single dimension made up of 20 items. In addition, the results show that there is a positive and statistically significant association between the perception of family functioning and resilience, where family functionality predicts to a certain degree the ability of late adolescents from Metropolitan Lima to be resilient.